Психологическое здоровье детей дошкольного возраста в условиях многообразия - Александрова, Марина Викторовна; Александрова, Наталья Викторовна (International Dialogues on Education Journal, 2017)
The article discusses some aspects of children’s mental health problems in the context of the contemporary socio-cultural situation. It is shown that the conditions for the development of today’s children have a significant impact on their mental health. These include: the reduction of the childhood period due to early learning, the absorption of childhood by adult culture, fragmentation and individualism, the need to adapt quickly to changing conditions, and others.). There is a need to identify the resources for modern social and cultural situations, which would become a source of maintaining and strengthening the children’s mental health, for their full development. Caring for children’s mental health requires the accommodation for the full childhood period, personal identity development, and interpersonal relations, formation of a moral position, development of reflective and cognitive personality spheres, the development of games and other children’s activities, and developing effective coping strategies.